Public Health Consequences on Vulnerable Populations from Acute Chemical Releases - Perri Zeitz Ruckart; Maureen F. Orr (SAGE Publishing, 2008)
Data from a large, multi-state surveillance system on acute chemical releases were analyzed to describe the type of events that are potentially affecting vulnerable populations (children, elderly and hospitalized patients) in order to better prevent and plan for these types of incidents in the future. During 2003-2005, there were 231 events where vulnerable populations were within ¼ mile of the event and the area of impact was greater than 200 feet from the facility/point of release. Most events occurred on a weekday during times when day care centers or schools were likely to be in session. Equipment failure and human error caused a majority of the releases. Agencies involved in preparing for and responding to chemical emergencies should work with hospitals, nursing homes, day care centers, and schools to develop policies and procedures for initiating appropriate protective measures and managing the medical needs of patients. Chemical emergency response drills should involve the entire community to protect those that may be more susceptible to harm.